2000
DOI: 10.2134/agronj2000.923493x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage × Rotation × Management Interactions in Corn

Abstract: Although corn (Zea mays L.) yields following soybean [Glycine max (L.) Merr.] or wheat (Triticum aestivum L.) exceed yields of continuous corn, continuous corn is common in the northeastern USA because of demand for corn by the dairy industry. We evaluated corn under different tillage (moldboard plow, chisel, and ridge), rotation (continuous corn, soybean–corn, soybean–corn–corn, and soybean–wheat/red clover (Trifolium pratense L.)–corn), and management systems (high and low chemical input) for 6 yr to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The ERS data are based on USDA's National Agricultural Statistical Service (NASS) agricultural chemical usage data sets. These data do not differentiate across crop rotations, even though there is agronomic evidence that continuous corn needs to receive higher levels of fertilizer (Raimbault and Vyn 1991, Katsvairo and Cox 2000, Pikul et al 2005. Unfortunately, there is little historical large scale data on the management of continuous corn rotations.…”
Section: Economic Modeling Componentmentioning
confidence: 99%
“…The ERS data are based on USDA's National Agricultural Statistical Service (NASS) agricultural chemical usage data sets. These data do not differentiate across crop rotations, even though there is agronomic evidence that continuous corn needs to receive higher levels of fertilizer (Raimbault and Vyn 1991, Katsvairo and Cox 2000, Pikul et al 2005. Unfortunately, there is little historical large scale data on the management of continuous corn rotations.…”
Section: Economic Modeling Componentmentioning
confidence: 99%
“…The greater the diversity and number of tactics adopted, the more successful and durable the overall weed management program becomes . Generally, the combination of many tactics provides better weed management than the simple addition of individual tactics …”
Section: Adoption Of Selected Iwm Strategies To Manage Hr Weedsmentioning
confidence: 99%
“…However, for more complex crop rotation schemes, one crop without a herbicide treatment may not negatively affect the overall reduction in the weed seedbank. Tillage as part of a crop rotation system can improve weed management, crop yield and profitability (Table ) . Crop rotation used for HR weed management was reported to be effective for 97% of the respondents to the 2013 Iowa Farm and Rural Life Poll (Table ) .…”
Section: Adoption Of Selected Iwm Strategies To Manage Hr Weedsmentioning
confidence: 99%
“…silvinomoreira@dag.ufsj.br. aggregating this nutrient to the straw, which, when decomposed, supplies the N to the successive crop (ALMEIDA et al, 2008;TORRES;PEREIRA;FABIAN, 2008). Long-term studies have demonstrated higher corn yield in rotation with soybeans, even under restricted nutrients availability, when compared with monocultures with adequate nutritional supply (KATSVAIRO;COX, 2000;STANGER;LAUER, 2008).…”
Section: Introductionmentioning
confidence: 99%